2023
DOI: 10.26417/ejes.v5i1.p7-14
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction in the Health Care Sector: Empirical Evidence from Medical Care in Greece

Abstract: It is extremely important for employees in every sector of an economy to be satisfied with their work since job satisfaction contributes significantly to improvements in their productiveness and performance. This paper deals with the very sensitive sector of health care in which medical staff provide citizens with health care services. The job satisfaction of these medical care providers is of particular importance when aiming to improve the quality of their services. Literature on job satisfaction among the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(26 reference statements)
2
0
0
Order By: Relevance
“…The significance of the extrinsic and intrinsic characteristics for job satisfaction has been demonstrated in several professions [ 45 , 47 ], including teachers [ 12 , 39 , 48 ]. The significance of extrinsic job characteristics (e.g., working conditions, wages) on the level of job satisfaction of teachers has been observed in other countries [ 3 , 49 ]; this was also observed in the present work, and extrinsic job characteristics were also a significant source of stress for the teachers who participated in the present work. Similar results have been reported from teachers working in public schools in Greece [ 5 , 12 ].…”
Section: Discussionsupporting
confidence: 82%
“…The significance of the extrinsic and intrinsic characteristics for job satisfaction has been demonstrated in several professions [ 45 , 47 ], including teachers [ 12 , 39 , 48 ]. The significance of extrinsic job characteristics (e.g., working conditions, wages) on the level of job satisfaction of teachers has been observed in other countries [ 3 , 49 ]; this was also observed in the present work, and extrinsic job characteristics were also a significant source of stress for the teachers who participated in the present work. Similar results have been reported from teachers working in public schools in Greece [ 5 , 12 ].…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, we believe that empowerment of management, achievement, promotion and evaluation should significantly improve job satisfaction respectively. This study showed that obtained factors are aligned with the findings of the prior studies in the literature [60,61].…”
Section: Discussionsupporting
confidence: 87%